Pelatihan SADARI sebagai Upaya Menekan Angka Kanker Payudara pada Siswi SMAN 13 Maros - Sartika Sartika; Halida Thamrin; Andi Sani (Pusat Riset dan Inovasi Nasional, 2023)
: Breast cancer is a malignant disease in the world and is the main cause of death from breast cancer among women. Breast cancer can be detected at an early stage which can be done by BSE. Even though the examination is based on existing guidelines and tutorials, with BSE more early stage breast cancer can be detected. However, teenagers feel afraid and feel that they lack knowledge regarding BSE.This community service aims to increase students' knowledge about the BSE method, increase the ability and skills to apply the BSE method independently, provide information boards in the UKS room. This activity involved 23 female students from SMAN 13 Maros. The approach method used is counseling and training on the BSE method.Breast cancer is a malignant disease in the world and is the main cause of death from breast cancer among women. Breast cancer can be detected at an early stage which can be done by BSE. Even though the examination is based on existing guidelines and tutorials, with BSE more early stage breast cancer can be detected. However, teenagers feel afraid and feel that they have minimal knowledge regarding BSE. This community service aims to increase students' knowledge about the BSE method, increase the ability and skills to apply the BSE method independently, provide information boards in the UKS room. This activity involved 23 female students from SMAN 13 Maros. The approach method used is counseling and training on the BSE method. The results of the outreach activities showed that students' knowledge and abilities changed from negative to positive by 68.2% through pretest and posttest questionnaires. It is hoped that schools can initiate the formation of student health groups and routinely carry out activities that increase students' knowledge about adolescent health.